Urban planning protection of the cultural heritage objects in Kozelshchyna town, Poltava region - Osychenko, Halyna; Khliupin, Oleksandr (Budownictwo i Architektura, 2025)
Ensuring the preservation of historical and cultural heritage has become a significant challenge for small towns in the era of globalisation and urbanisation. Protection zones (buffer zones) of cultural heritage objects (CHOs) are the primary means of urban planning protection, helping to safeguard the authenticity and individuality of small towns while ensuring their sustainable development. This article presents the results of developing measures for the urban planning protection of the town of Kozelshchyna in the Poltava region, Ukraine. The town’s historical development was studied, cultural heritage objects were identified, and a comprehensive assessment of the Kozelshchyna territories was conducted. Using an integral methodology, the authors substantiated and defined the boundaries and usage regulations for the historical area and monument protection zones of Kozelshchyna. The proposed usage regulations and requirements for new construction aim to balance new developments with the preservation of historical heritage, integrating both aspects into the town’s future urban development. The study serves as a foundation for the development of the town's master plan and the concept for the monastery complex's future development.